2016
DOI: 10.1002/mrc.4486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic pore surface coating on the NMR relaxation and diffusion signal in quartz sand

Abstract: Magnetic impurities are ubiquitous in natural porous media such as sand and soil. They generate internal magnetic field gradients because of increased magnetic susceptibility differences between solid and liquid phase in the pore space and because of the presence of magnetic centers. These internal gradients accelerate NMR relaxation rates and thus might limit the possibility of pore space characterization using NMR. In this study, we investigate the effects of coating the surface of natural sands by the antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
(134 reference statements)
2
8
0
Order By: Relevance
“…reported that a similar goethite coating technique produced a 75% surface coverage on the sand. Similarly, Duschl et al reported that our goethite coating technique produced a high goethite surface density of 6 to 27 particles per μm 2 . Collectively, the literature and Figure S1 indicate a high density of goethite particles coated the GQS.…”
Section: Resultssupporting
confidence: 55%
“…reported that a similar goethite coating technique produced a 75% surface coverage on the sand. Similarly, Duschl et al reported that our goethite coating technique produced a high goethite surface density of 6 to 27 particles per μm 2 . Collectively, the literature and Figure S1 indicate a high density of goethite particles coated the GQS.…”
Section: Resultssupporting
confidence: 55%
“…Peak 2 arises from the fast exchanges among large pores, and Peak 1 is mainly resulted from the relaxation in very small pores which have slow exchanges with other pores. Similar bimodal phenomena have also been identified in previous studies. , The T 2 value of Peak 2 for the calcite specimen is 102.341 ms, while for the silica specimen, it is 95.477 ms at t e = 0 min. As the t e increases, which corresponds to the decrease of water content, Peak 1 and Peak 2 gradually move left and finally merge to one peak when t e is 25 min for calcite and 20 min for silica specimens, and later, the merged peak continues to move left.…”
Section: Resultssupporting
confidence: 87%
“…In the conversions, the ratio of pore volume to pore surface area (V p /S p ) and transverse surface relaxivity (ρ 2 ) are assumed to be r/3 and 30 μm/s. 30 It is observed that, for the three samples, the amplitude of T 2 time in the slow relaxation domain (right side) is much larger than that of the fast relaxation domain (left side).…”
Section: Resultsmentioning
confidence: 84%
“…To show the pore size distributions (PSDs) of the tested samples, the T 2 relaxation time was converted to the pore radius based on the correlation in eq , then added into Figure with an upper-X-coordinate. In the conversions, the ratio of pore volume to pore surface area ( V p / S p ) and transverse surface relaxivity (ρ 2 ) are assumed to be r /3 and 30 μm/s . It is observed that, for the three samples, the amplitude of T 2 time in the slow relaxation domain (right side) is much larger than that of the fast relaxation domain (left side).…”
Section: Resultsmentioning
confidence: 99%